DISTINCTIVE [VOICE] DOES NOT IMPLY REGRESSIVE ASSIMILATION:EVIDENCE FROM SWEDISH - Ringen, Catherine; Helgason, Pétur (International Journal of English Studies, 2009)
In a recent paper, van Rooy & Wissing (2001) distinguish between the "broad interpretation" and the "narrow interpretation" of the feature [voice]. According to the broad interpretation, languages with a two way [voice] contrast may implement this contrast phonetically with any two of the following: voice onset precedes plosive release (prevoicing), voice onset immediately follows plosive release, voice onset substantially lags behind plosive release. According to the narrow interpretation, [voice] is employed only in languages with prevoicing in word-intial stops. According to van Rooy & Wissing, languages with prevoicing always have onlyregressive voice assimilation. The purpose of this paper is twofold: First we show that Swedish employs the feature [voice] on the narrow interpretation, but does not have regressive voice assimilation. Second, we present an OT account of the Swedish data which involves both features [voice] and [spread glottis].